Kant's Third Critique: The Project of Unification. (19th July 2016) - Gardner, Sebastian
Abstract: This paper offers a synoptic view of Kant's Critique of the Power of Judgement and its reception by the German Idealists. I begin by sketching Kant's conception of how its several parts fit together, and emphasize the way in which the specifically moral motivation of Kant's project of unification of Freedom and Nature distances it from our contemporary philosophical concerns. For the German Idealists, by contrast, the CPJ 's conception of the opposition of Freedom and Nature as defining the overarching task of philosophy provides a warrant and basis for bold speculative programmes. The German Idealist development therefore presupposes Kant's failure in the CPJ to resolve the problem of the relation of Freedom and Nature. What is fundamentally at issue in the argument between Kant and his successors is the question of the correct conception of philosophical systematicity and in this context I reconstruct Kant's defence of his claim to philosophical finality.